Refractive lens exchange on keratoconus patient: a case report - Ivane Jessica Buddyman; Cokorda Istri Dewiyani Pemayun; Ariesanti Tri Handayani (Intisari Sains Medis, 2021)
Introduction. Keratoconus is a vision disorder that occurs when the cornea becomes thin and irregularly (cone) shaped. Instead of being focused correctly on the retina, this abnormal shape causes the light entering the eye to improperly refracted and manifested as a distortion of vision. Refractive Lens Exchange is one type of Invasive therapy in Keratoconus. Here we describe a case of Keratoconus managed by the Refractive Lens Exchange procedure in our Center.Case Description. A male, 25 years old, visited the clinic due to blurry vision since ten years ago. Every six months or a year, he needs to adjust his lens power. Ophthalmology examination found visual acuity in the right eye was 2/60 PH 6/60, and if using S-9.00, visual acuity improved to 6/30. Meanwhile, visual acuity in the left eye was 1/60 PH 6/60 and if using S–11.75, visual acuity improved to 6/48. Corneal topography supports the finding of Keratoconus. Management for this patient was Refractive Lens Exchange + Intraocular Lens + Capsular Tension Ring. Initially, This  advised was differ from the patient expectation, as he wanted a LASIK procedure. An important reminder was given, that Keratoconus is contraindicated for LASIK and any corneal surface ablation procedure. After series of procedure, the VA of the right eye was 6/15 PH 6/6, with C - 4.00 x 1800 VA became 6/6. VA left eye was 6/18 PH 6/9, with C - 4,00 x 1800 VA became 6/9. Binocular vision was 6/6. For near vision, S +3.00 was added for both eyes.Conclusions. Refractive Lens Exchange + Intraocular lens implantation is effective and safe procedures to treat high myopia in keratoconus cornea.